Celastrol enhances transcription factor EB (TFEB)-mediated autophagy and mitigates Tau pathology: Implications for Alzheimer's disease therapy - Chuanbin Yang; Chengfu Su; Ashok Iyaswamy; Senthil Kumar Krishnamoorthi; Zhou Zhu; Sichang Yang; Benjamin Chunkit Tong; Jia Liu; Sravan G. Sreenivasmurthy; Xinjie Guan; Yuxuan Kan; Aston Jiaxi Wu; et al. (Acta Pharmaceutica Sinica B, 2022)
Alzheimer's disease (AD), characterized by the accumulation of protein aggregates including phosphorylated Tau aggregates, is the most common neurodegenerative disorder with limited therapeutic agents. Autophagy plays a critical role in the degradation of phosphorylated Tau aggregates, and transcription factor EB (TFEB) is a master regulator of autophagy and lysosomal biogenesis. Thus, small-molecule autophagy enhancers targeting TFEB hold promise for AD therapy. Here, we found that celastrol, an active ingredient isolated from the root extracts of Tripterygium wilfordii (Lei Gong Teng in Chinese) enhanced TFEB-mediated autophagy and lysosomal biogenesis in vitro and in mouse brains. Importantly, celastrol reduced phosphorylated Tau aggregates and attenuated memory dysfunction and cognitive deficits in P301S Tau and 3xTg mice, two commonly used AD animal models. Mechanistical studies suggest that TFEB-mediated autophagy-lysosomal pathway is responsible for phosphorylated Tau degradation in response to celastrol. Overall, our findings indicate that Celastrol is a novel TFEB activator that promotes the degradation of phosphorylated Tau aggregates and improves memory in AD animal models. Therefore, Celastrol shows potential as a novel agent for the treatment and/or prevention of AD and other tauopathies.